Answer: 258
Step-by-step explanation:
86 times 3=258
Answer:
is the answer
Step-by-step explanation:
Equation of the line: y = 6/5x + 1
= 5y = 6x + 5
= 6x - 5y + 5
Equation of the perpendicular line: bx - ay + k = 0
= -5x -6y + k = 0
Equation passes through (6,-6),
-5(6) -6(-6) + k = 0
-30 + 36 + k = 0
6 + k = 0
k = -6
Substituting,
-5x -6y + k = 0
-5x -6y -6 = 0
-6y = 5x + 6
(Slope-Intercept form)
Answer:
1st pic: Answer is 3
2nd pic: Answer is 5
3rd pic: Answer 4
Step-by-step explanation:
Speak in English please. I would be more pleased to help if you write in English.